The Effects of Seleno-Methionine in Cadmium-Challenged Human Primary Chondrocytes - Valentina Urzì Brancati; Federica Aliquò; José Freni; Alice Pantano; Erika Galipò; Domenico Puzzolo; Letteria Minutoli; Herbert Ryan Marini; Giuseppe Maurizio Campo; Angela D'Ascola (MDPI AG, 2024)
Cadmium (Cd) is a potentially toxic element able to interfere with cellular functions and lead to disease or even death. Cd accumulation has been demonstrated in cartilage, where it can induce damage in joints. The aim of this study was to evaluate the effect of CdCl2 on primary cultures of human chondrocytes and the possible protective effect of seleno-methionine (Se-Met). Human primary articular chondrocytes were cultured and treated as follows: control groups, cells challenged with 7.5 μM and 10 μM CdCl2 alone, and cells pretreated with 10 and 20 μM Se-Met and then challenged with 7.5 μM and 10 μM CdCl2. Twenty-four hours after incubation, cell viability, histological evaluation with hematoxylin-eosin stain, and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay were performed. Furthermore, reverse transcription-PCR was carried out to evaluate mRNA levels of BAX, BAK1, CASP-3, and CASP-9. After CdCl2 challenge at both doses, a reduced cell viability and an overexpression of BAX, BAK1, CASP-3, and CASP-9 genes, as well as a high number of TUNEL-positive cells, were demonstrated, all parameters becoming higher as the dose of CdCl2 was increased. The pretreatment with Se-Met lowered the expression of all considered genes, improved cell viability and morphological changes, and reduced the number of TUNEL-positive cells. It was concluded that Se-Met plays a protective role against CdCl2-induced structural and functional changes in chondrocytes in vitro, as it improved cell viability and showed a positive role in the context of the apoptotic pathways. It is therefore suggested that a translational, multifaceted approach, with plant-based diets, bioactive functional foods, nutraceuticals, micronutrients, and drugs, is possibly advisable in situations of environmental pollution caused by potentially toxic elements.